ISLAMIC SCIENCE TECHNOLOGY BASED ENVIRONMENTAL MANAGEMENT MATERIAL TEACHING MODULE TO IMPROVE 6C - Siti Fatimah; Ospa Pea Yuanita Meishanti; Muhamad Khoirur Roziqin (GeoEco, 2024)
Developing learning media at the junior high school level is the focus of this research. The importance of information and communication technology is to support students in learning activities and create interesting media for learning. This teaching module discusses the importance of maintaining human behavior to live in harmony with nature. By instilling the nature of caring for the environment in students, it will grow a sense of mutual care and prevent damage to the natural environment. This study aims to develop a teaching module for the Pancasila Student Profile for educators implementing the Merdeka Curriculum. The Merdeka Curriculum includes 6C skills which is an addition to the role of skills 21st century. The teaching module developed by this researcher is differentiated, namely PAI with IPA. The method used is the R&D research and development method. This research is used to validate and develop a learning media that adapts the 4D model, namely define, design, develop, and disseminate by distributing learning media feasibility questionnaires. This research involved biology lecturers, PAI teachers, and biology teachers. The evaluation of the Islamic science technology-based environmental management module resulted in high feasibility percentages of 90%, 96.25%, and 98.75%. With a very feasible category, this teaching module can be used as an attractive learning media to support the learning process, thereby improving student learning outcomes. Therefore, the author recommends this development research be used as a reference for further research related to learning media in the form of teaching modules for the Merdeka Curriculum.